2024
DOI: 10.1002/zoo.21829
|View full text |Cite
|
Sign up to set email alerts
|

Weight as an indicator of enclosure suitability in Livingstone's fruit bats (Pteropus livingstonii)

Eluned C. Price,
Alex Roberts,
Laura Bennett
et al.

Abstract: Obesity is common in zoo animals, and both dietary management and the provision of adequate opportunities for exercise are needed to tackle it. We used 30 years of records from Jersey Zoo to compare the weight and forearm length of wild and captive‐born Livingstone's fruit bats (Pteropus livingstonii), and to assess the impact on weight of enclosure space. The mean capture weight of wild‐caught male Livingstone's bats was 657 g, significantly higher than that of females (544 g). In both wild and captive‐born b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Bats older than ten years old were not observed performing any flying behaviour, possibly due to their dominance rank, which renders them more likely to be sedentary and control a territory [17,27]. It has recently been shown that bats living in smaller enclosures are more likely to have a higher body mass, presumably due to their limited opportunities to fly [16], again supporting our expectation of reduced locomotion correlating with higher body mass. Additionally, reluctance to fly and lethargy are two of the clinical signs of cardiomyopathy in Pteropus species described by Killick et al (2017).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Bats older than ten years old were not observed performing any flying behaviour, possibly due to their dominance rank, which renders them more likely to be sedentary and control a territory [17,27]. It has recently been shown that bats living in smaller enclosures are more likely to have a higher body mass, presumably due to their limited opportunities to fly [16], again supporting our expectation of reduced locomotion correlating with higher body mass. Additionally, reluctance to fly and lethargy are two of the clinical signs of cardiomyopathy in Pteropus species described by Killick et al (2017).…”
Section: Discussionsupporting
confidence: 77%
“…This would be especially true when subordinates are foraging as they might need to enter a dominant individual's territory; bats that frequently move between social groups are known to have higher cortisol levels in this species, highlighting that perceived levels of risk can be higher in these individuals [30]. Individuals with a larger body mass are likely to be showing reduced vigilance behaviour as they are more likely to be territory holders and therefore hold a higher dominance rank (as body mass, age, and dominance rank are positively correlated in this species; [16,28], with less need to socially monitor others. Particularly low levels of vigilance behaviour could indicate higher body mass in this species, meaning this behaviour could be used by keepers as an indicator of risk of cardiomyopathy; males that are showing low levels of vigilance have more time for foraging and therefore weight gain.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations